Implantable loop recorder in unexplained syncope: classification, mechanism, transient loss of consciousness and role of major depressive disorder in patients with and without structural heart disease. Issue 4 (18th October 2007) - Pezawas, T; Stix, G; Kastner, J; Schneider, B; Wolzt, M; Schmidinger, H
Abstract : Objective: To stratify mechanisms and predictors of unexplained syncope documented by an implantable loop recorder (ILR) in patients with and without structural heart disease (SHD). Design and setting: Prospective study in consecutive patients of a university cardiac centre. Patients and methods: An ILR was implanted in 70 patients (34 male/36 female, aged 55 (17) years) in whom syncope remained unexplained after thorough testing. SHD was present in 33 patients (ischaemic cardiomyopathy in 16, dilated cardiomyopathy in 9 and hypertrophic cardiomyopathy in 8) and absent in 37 patients (mean (SD) left ventricular ejection fraction 46 (4)% vs 61 (7)%, respectively). Results: A syncopal recurrence occurred during 16 (8) months in 30 patients (91%) with SHD and in 30 patients (81%) without SHD. Fifteen patients (45%) versus 19 patients (51%), respectively, had an ILR-documented arrhythmia at the time of recurrence which led to specific treatment. The remaining 15 patients (45%) with SHD and 11 patients (30%) without SHD had normal sinus rhythm at the time of the recurrence. On stepwise multivariate analysis only major depressive disorder was predictive for early recurrence during ILR follow-up (p = 0.01, hazard ratio  =  3.35, 95% CI 1.1 to 7.1). Fifty seven per cent of patients with major depressive disorder had sinus rhythm during recurrence compared with 31% of patients without the disorder (p = 0.01). Conversely, no patient with major depressive disorder had asystole compared with 33% without (p<0.001). Conclusions: The presence of SHD has little predictive value for the occurrence or type of arrhythmia in patients with unexplained syncope. Patients with major depressive disorder are prone to early recurrence of symptoms and have no evidence of arrhythmia in most cases. The ILR leads to specific treatment in half of all patients.